Moderasi Beragama dalam menghadapi ideologi transnasional dan implikasinya terhadap kedisiplinan siswa - Revaldy, Aries Dimas; Maarif, Muhammad; Yusuf Suharto (Indonesian Journal of Islamic Religious Education, 2024)
This study aims to analyze the strategy of cultivating religious moderation amidst the rapid influence of transnational ideologies in improving student discipline at SD Negeri 17 Pemecutan. This research uses a descriptive qualitative approach with the phenomenological method to understand the essence of students‘ and teachers’ experiences related to religious moderation and its impact on discipline. Data were collected through observation, interviews, and documentation to explore the implementation of strategies carried out by teachers in dealing with transnational ideologies and instilling moderate attitudes in religion. The results showed that one of the effective strategies is through activities such as flag ceremonies that foster a sense of love for the country and interfaith learning that emphasizes tolerance and mutual respect. Teachers also have an important role in developing student discipline through personal approaches and providing opportunities for students to explore their talents through extracurricular activities. This research provides new insights into the importance of religious moderation in shaping students' characters who are disciplined and respectful of differences. In conclusion, this strategy needs to be implemented sustainably to form an ethical, well-mannered generation, and aware of diversity.